Nanosensors based on lignocellulosic materials - Dalkilic, Berk; Durmaz, Ekrem; Oncul, Bartu; Candan, Zeki (BioResources, 2024)
In recent years, lignocellulosic materials have become regarded as attractive and noteworthy natural resources owing to their renewability, recyclability, easy processability, abundance, biodegradability, and low cost. The developments in nanotechnology have opened new doors in the field of bio-based nanosensor technology, which is utilized in electronics, optical products, communication, automotive, packaging, tissue engineering, biomedical, textile, etc. This paper mainly focuses on the usage of lignocellulosic materials in nanosensors.
Keywords: Biomaterials; Sustainability; Circular economy; Sensors; Nanolignin; Nanocellulose; 7. Clean energy